Design and analysis of 2T2M hybrid CMOS-Memristor based RRAM. (March 2018) - Shaarawy, Noha; Emara, Ahmed; El-Naggar, Ahmed M.; Elbtity, Mohammed E.; Ghoneima, Maged; Radwan, Ahmed G.
Abstract: In this paper, a Static Noise Margin (SNM) analysis for 2T2M RRAM cell is investigated. The proposed analysis is done using mathematical formulation and verified by SPICE simulations. The analysis is tested for both, write and read modes. Moreover, the analysis is applied to diverse types of RRAM cells, and a comparison between the performance of such cells is discussed. Additionally, the effect of the exponential memristor model on the memristor behaviour in terms of switching speed and the range of the memristor resistance are discussed in detail. The circuits design and simulations were carried out using TSMC 130 nm CMOS technology and Cadence Virtuoso tool. Finally, comparison between different RAM technologies is briefly presented.